A New Enthalpy of Formation Test Set Designed for Organic Fluorine Containing Compounds. Issue 8 (6th May 2022) - Si, Yitao; Liu, Yingzhe; Lai, Weipeng; Ma, Yiding; Shi, Jinwen; Wang, Bozhou; Liu, Maochang; Yu, Tao
Abstract: The deviations of gas phase enthalpy of formation predicted by density functional theory on the fluorine containing system are larger than those on other systems in most cases. Therefore, an enthalpy of formation test set composed of 41 organic fluorine containing compounds is proposed, and in this work it is called OFCC41 test set. Twenty exchange‐correlation functionals are estimated by CCSD(T)/CBS as benchmark. The first part of the results indicates that CAM‐B3LYP, ωB97X, and M06 are the most suitable functionals to predict enthalpies of formation for fluorine containing compounds. The remainder of this work is primarily concerned with diffuse basis sets and size‐dependent effects. Diffuse basis sets ma‐SVP and ma‐TZVP can generally improve the prediction performance. For very small molecules, using ma‐SVP is sufficient while for larger molecules more completed basis sets are demanded. Size‐dependent effect of prediction accuracy on different molecules is revealed by using a simple strategy, that the different sizes of molecules are distinguished with three intervals and given the corresponding mean absolute errors. This study provides a test set designed for organic fluorinated compounds and contributes to the selection of some functionals suitable for fluorine containing system. Abstract : A new enthalpy of formation test set specialized in fluorine containing molecules is built with the reference of CCSD(T)/CBS. Density functional theory calculation performance evaluations of different functionals are conducted to see which functionals can be applied to fluorine containing systems, and some features of this test set are also briefly concluded.